Dionysus' Victim: The Pentheus Myth beyond Euripides - Bednarek, Bartłomiej, (Classical Studies E-Books Online, Collection 2025., 2026)
This book investigates ancient texts of culture about Pentheus. It includes a section devoted to the rigorous Quellenforschung and a detailed analysis of the stylistic and thematic features of each of them. The results of the author's inquiry are original and thought provoking as he argues that in the vast majority of cases the scholarly tradition, according to which authors engaged in a direct intertextual dialogue with Euripides, is not tenable. Having established this, the author turns to specific features of each text and image in order to inquire about the meaning and function that Pentheus' myth played in them.